Utilising Public Finance to Foster Sustainable Growth in Local Communities - Kyrylenko, Olga; Gavkalova, Nataliia; Shashkevych, Oleksandr; Humen, Volodymyr; Onyshchuk, Serhii (European Journal of Sustainable Development, 2025)
Due to fiscal decentralisation in Ukraine, local finances have become a more significant component of public finances, gaining a greater degree of autonomy and potential to be used to ensure the resilience and sustainable development of territories. At the same time, in the context of the war, communities faced the need to reorient their budgets towards the public order and social sectors, while spending on environmental protection and development incentives was significantly reduced. Sustainable development strategies were also suspended. The article aims to highlight current trends and the state of public finance as a tool for ensuring the sustainable development of territorial communities. Methods. The article used statistical analysis methods to assess the dynamics and structure of public finances in Ukraine in 2018–2024 and the case study method to review the strategies for sustainable development of territorial communities and sources of their financing. The results demonstrate increased state budget revenues in 2018–2024 and their share in public finances. Local budget revenues have fluctuated over this period, and their share has decreased. The amalgamation of territorial communities in 2020 contributed to financial consolidation, resulting in increased community budget revenues and their share in the structure of local budgets. The volume of community expenditures has also increased since 2018, and the possibilities for financing the socio-economic development of the territories have significantly expanded. The experience of local communities in Ukraine shows that local authorities have different priorities in their territorial development activities: some communities focus on economic growth, entrepreneurship, and investment, while others focus on social services, public order and security, and social protection. The concentration of financial resources in municipalities has expanded the possibilities for implementing local programmes and projects, including sustainable development projects. At the same time, there is a differentiation in the funding sources for sustainable development strategies, and community budgets and government transfers remain key to their implementation. The practical value of the study lies in highlighting trends, the state of public finances in Ukraine at the state and local levels, the state of development of sustainable community development strategies, and sources of funding. Keywords: public finance, financial potential of territorial communities, local budget expenditures on social protection, fiscal policy, financial control.